Hydrochemistry and fluoride contamination in Ndali-Kasenda crater lakes, Albertine Graben: Assessment based on multivariate statistical approach and human health risk - Ojok, Walter; Wanasolo, William; Wasswa, John; Bolender, James; Ntambi, Emmanuel (Groundwater for Sustainable Development, 2021)
Hydrochemistry of crater lakes (n = 15) in the Ndali-Kasenda cluster was deciphered using standard methods of the American Public Health Association to understand the major ion chemistry; spatial distribution, occurrence, and non-carcinogenic health risks due to exposure to fluoride levels in the lakes in Ndali- Kasenda cluster, Albertine Graben. Numerous economic activities take place in and around the crater lakes which serve as major sources of domestic water whose origin of potential contaminants is ambiguous. In this study, WHO (2017) regulatory limit exceedance included F􀀀 , pH, Ca2+, Fe2+, Mn2+, and TDS. A strong positive correlation was observed between F􀀀 and TDS; F􀀀 and pH; F􀀀 and EC; F􀀀 and HCO3􀀀 . However, concerning hydrogeochemical signature, the lakes are mainly of Ca–HCO3 type and low in Na–K–HCO3 type due to rock water interaction in the geology of the area. Principal component analysis (PCA) performed on Ndali-Kasenda hydrogeochemical data resulted in six principal components (PCs) explaining 88.6% of the total variance. The PCs represented the primary processes that control the crater lake hydrogeochemistry in the Ndali-Kasenda area which include; weathering of rocks reactions, ion exchange, and evaporation processes. The hazard quotient (HQ) for non-carcinogenic health risks associated with exposure to Ndali- Kasenda fluoride levels via ingestion revealed that HQ for infants surpassed the acceptable HQ limit for all the lakes studied, while 86.67 % of the sampled lakes exceeded the HQ value for children via ingestion. Based on the hydrogeochemical parameters analyzed, aside from L. Murigamire and L. Wankenzi, water from the other studied lakes is chemically not acceptable for drinking purposes. An urgent need to take ameliorative action in this area to protect the inhabitants from exposure to excess fluoride in drinking water was recommended.
Keywords: Fluoride; Ndali-kasenda; Albertine graben; Hydrochemistry; Multivariate statistics; Crater lakes